Bioprocess and genetic engineering aspects of ascomycin production: a review - Krishika Sambyal; Rahul Vikram Singh (Journal of Genetic Engineering and Biotechnology, 2020)
Abstract Background Ascomycin is a highly valuable multifunctional drug which exhibits numerous biological properties. Being an immunosuppressant, it is known to prevent graft rejection in humans and has potential to treat varying skin ailments. Its derivatives represent a novel class of anti-inflammatory macrolactams. But the biosynthetic machinery of ascomycin is still unclear. Main body of the abstract Due to the structural complexity, there occurs difficulty in its chemical synthesis; therefore, microbial production has been preferred by using Streptomyces hygroscopicus subsp. ascomyceticus. Through several genetic manipulation and mutagenesis techniques, the yield can be increased by several folds without any difficulties. Genetic engineering has played a significant role in understanding the biosynthetic pathway of ascomycin. Short conclusion Recently, many efforts have been made to utilize the therapeutic effects of ascomycin and its derivatives. This article covers concepts related to the production kinetics of ascomycin including an update of the ongoing yield improvement techniques as well as screening method of novel strains for ascomycin production.